Examining the Effects of Multiple Leadership Styles on Organizational Performance Through Employee Engagement in Nepal - Mishra, Uttam; Mishra, Udgam; Kapair, Rekha (Journal of Research and Development, 2026)
This study examines how four leadership styles, transformational, ethical, strategic, and transactional affect organisational performance in Nepalese organisations, with employee engagement as a mediator. Using a quantitative, cross-sectional design, data were collected from 374 employees and managers in organisations located in Biratnagar, Itahari, and Dharan. Stratified random sampling ensured representation across public sector institutions, private firms, and non-governmental organisations. Structural equation modelling (SEM) was conducted using SPSS 26.0 and AMOS 26.0, following a two-step analytical approach. The measurement model confirmed satisfactory reliability and convergent validity for all the constructs. The structural model revealed that transformational (β = .312, p < .001), ethical (β = .248, p < .001), strategic (β = .289, p < .001), and transactional (β = .198, p < .001) leadership styles positively predicted organizational performance. Employee engagement partially mediated all four of these relationships. Transformational leadership produced the largest indirect effect through engagement (β = .134), followed by ethical (β = .106), strategic (β = .091), and transactional leadership (β = .075), respectively. The leadership styles jointly explained 51.2% of the variance in employee engagement and 63.4% of the variance in organizational performance. These findings extend the emerging economy leadership literature to the South Asian federal context and offer actionable guidance for organisational leaders, human resource practitioners, and policymakers in Nepal.